Inverse Equation for original equation y=(3/4)x-1

River

New member
Joined
Jan 12, 2016
Messages
2
This problem is an inverse equation and I'm stuck on the division part, The problem is y=(3/4)x-1
First I swapped y and x so it became x=(3/4)y-1
Next I added 1 to each side resulting in x +1=(3/4)y
Finally I attempted at dividing 3/4 or multiplying each side by 4, but I couldn't figure out the correct answer. Please help and thank you for your time!
 
This problem is an inverse equation and I'm stuck on the division part, The problem is y=(3/4)x-1
First I swapped y and x so it became x=(3/4)y-1
Next I added 1 to each side resulting in x +1=(3/4)y
Finally I attempted at dividing 3/4 or multiplying each side by 4, but I couldn't figure out the correct answer. Please help and thank you for your time!
What do you want to do? Do you want to find the inverse f-1(x) of the function
f(x) = y = (3/4)x - 1
or do you want to make x the subject of the above equation, i.e.
g(y) = x = ...?

Although either way you end up with the same linear equation in a mathematical sense, if it is the former, you are proceeding correctly and if it is the latter, then the notation is incorrect as Denis indicates.
 
Top